2010
DOI: 10.1021/jo100761k
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Charge Transfer in the Gas Phase: Fragmentation of Protonated Sulfonamides in Mass Spectrometry

Abstract: The fragmentation of protonated molecules (MH(+)) in mass spectrometry usually results in even-electron product ions, but the MH(+) ions of sulfonamides are different as they often produce dominant radical cations of the constituent amines. For a series of benzenesulfonamides of anilines that bear various substituents, we found that the sulfonamides are preferentially protonated at the nitrogen, which is different from the carboxylic amides. Upon N-protonation, the S-N bond dissociates spontaneously to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
74
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

7
3

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 68 publications
0
74
0
2
Order By: Relevance
“…Consequently, a need for other examples of INC-mediated reactions is evident in order to better understand the fragmentation reactions in the contemporary ESI mass spectrometry, a method that has become one of the most popular analytical methods. Thus, renewed interest in studies on INC-mediated fragmentation reactions has emerged in recent years [8,[20][21][22][23][24][25][39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a need for other examples of INC-mediated reactions is evident in order to better understand the fragmentation reactions in the contemporary ESI mass spectrometry, a method that has become one of the most popular analytical methods. Thus, renewed interest in studies on INC-mediated fragmentation reactions has emerged in recent years [8,[20][21][22][23][24][25][39][40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…It is significant and desirable to investigate the underlying mechanism of formation of OE ions from EE ions because such considerations are important for a better understanding of ESI mass spectrometry. In our recent work, we revealed that the formation of ionized anilines in the fragmentation of protonated benzenesulfonamides resulted from intramolecular charge transfer via an intermediate [sulfonyl cation/aniline] complex rather than a simple S-N bond homolysis [13].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, continuous efforts have been devoted to the investigation of the dissociation reactions of charged compounds derived from protonation [4][5][6][7][8] or deprotonation [9][10][11][12][13]. On the other hand, the mass spectrometric fragmentations of metal cationized, especially lithiated biomolecules, have attracted much attention because of the desire to measure intrinsic metal ion affinity and identify the binding sites [14,15], and because the interesting dissociation pathways exhibited by these compounds are usually different from the protonated and deprotonated analogues [16,17].…”
mentioning
confidence: 99%